Repeatable social network node‐based metrics across populations and contexts in a passerine. (11th October 2020) - Plaza, Mireia; Burke, Terry; Cox, Tara; Flynn‐Carroll, Alexander; Girndt, Antje; Halford, Georgina; Martin, Dominic A.; Sanchez‐Fortún, Moises; Sánchez‐Tójar, Alfredo; Somerville, Jasmine; Schroeder, Julia
Abstract: Behavioural traits are considered animal personality traits when individuals differ consistently in their expression across time and across context. Here, we test this idea on three metrics derived from social interaction networks (strength, betweenness and closeness). Using experimental data from house sparrows in captive populations, and observational data from house sparrows in a wild population, we show that all three metrics consistently exhibit repeatability across both study populations and two methods of recording interactions. The highest repeatability values were estimated in male‐only captive groups, whereas repeatabilities estimated in single‐sex networks subsetted from mixed‐sex groups showed no sex specificity. We also show that changes in social group composition led to a decrease in repeatability for up to six months. This work provides substantial and generalizable support for the notion that social network node‐based metrics can be considered animal personalities. Our work suggests that social network traits may be heritable and thus could be selected for. Abstract : Social network traits are consistent across time and contexts, in wild and captive house sparrows. That allows for the possibility of a heritable basis for social network traits. It also means that social network traits can be considered animal personality traits.